Probiótico em dietas de suínos sobre os parâmetros sanguíneos e digestibilidade de rações - Robles-Huaynate, Rizal Alcides [UNESP]; Thomaz, Maria Cristina [UNESP]; Santana, Aureo Evangelista [UNESP]; Iselda Hermans Masson, Guido Carlos [UNESP]; Amorim, Alessandro Borges [UNESP]; Silva, Susana Zaneti [UNESP]; Ruiz, Urbano dos Santos [UNESP]; Watanabe, Pedro Henrique [UNESP]; Lemos Budino, Fabio Enrique (Univ Estadual Londrina, 2014)
Two assays were accomplished being, both using a randomized block design: Assay 1 the aimed was to evaluate the blood parameters of weaned recently pigs and receiving rations with and without probiotic. Twenty pigs with body weight of 6.99 +/- 0.42 kg were used and were collected samples of blood to the 0, 7, 14, 21 and 28 days after wean, for determinations of the bool parameters. Assay 2 the objective was to determine the rations digestibility for growth swine supplemented or not with probiotic in the rations. The rations and the ages of the animals influenced most of the variables of the blood parameters. The probiotic didn't alter the ration digestibility to exception for mineral matter. It is ended that the blood parameters were altered for the use of the probiotic and the age of the animals, both emphasized to challenges happened after wean and the mineral matter was better taken advantage with the use of the probiotic.
Probiotic in swine diets on the blood parameters and rations digestibility
Keywords: Bacillus spp.; blood cells; mineral matter; stress; swine